VARIATIONS IN THE ELECTRIC FIELD AND TURBULENCE IN THE SURFACE ATMOSPHERIC LAYER - Koprov B.M.; Koprov V.M.; Anisimov S.V. (My University, 2006)
An experiment was carried out on the synchronous recording, in cloudless summer conditions in the middle region of Russia, of variations in the vertical component of electric field intensity E'; temperature; and the wind velocity components T', U', V', and W' . It was found that the correlation coefficient is positive between W' and E' and negative between U' and E'. If the temperature gradient sign changes to the opposite one, the correlation signs are retained, while the sign of the T' – E' correlation changes to the opposite one.